2018
DOI: 10.5539/ijel.v8n6p115
|View full text |Cite
|
Sign up to set email alerts
|

Oral Corrective Feedback: Investigating Kurdish High School Teachers’ Beliefs and Practices

Abstract: The current research explores the relationship between the beliefs and the actual classroom practices of the Kurdish teachers of English as a foreign language (EFL) regarding oral corrective feedback (OCF). To collect the data required, a questionnaire was administered to 8 Kurdish teachers of EFL of different academic qualifications from three different schools, and likewise a 5-hour audio-recorded classroom observation was carried out with the same sample. The findings revealed that almost all teachers' beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…On the other hand, Gómez Argüelles et al (2019) found that EFL teachers preferred giving oral CF at the end of the class, due to viewing immediate CF as having the potential to hurt their students" feelings. Alzeebaree1 et al (2018) found that Kurdish EFL teachers preferred to give their students immediate CF on their spoken errors. The students studied by Ananda et al (2017) also considered immediate oral CF to be the most effective strategy, believing that delayed CF led them to forget their errors.…”
Section: Efl Learners' Preferences Of Oral Cfmentioning
confidence: 99%
“…On the other hand, Gómez Argüelles et al (2019) found that EFL teachers preferred giving oral CF at the end of the class, due to viewing immediate CF as having the potential to hurt their students" feelings. Alzeebaree1 et al (2018) found that Kurdish EFL teachers preferred to give their students immediate CF on their spoken errors. The students studied by Ananda et al (2017) also considered immediate oral CF to be the most effective strategy, believing that delayed CF led them to forget their errors.…”
Section: Efl Learners' Preferences Of Oral Cfmentioning
confidence: 99%
“…Moreover, studies of oral corrective feedback should not focus solely on learning outcomes, but should also notice the learning process and make an attempt to identify the factors driving the effectiveness of oral corrective feedback (Jean & Simard, 2011). Other previous researches have examined teachers" beliefs about the time to give oral corrective feedback, such as Kurdish language teachers prefer to give their students immediate oral corrective feedback about their speaking errors (Alzeebareel et al, 2018). On the contrary, English foreign language students at a University in Thailand prefer their teachers to offer oral corrective feedback after completing their speaking task, claiming that this is the most effective time to correct speech errors (Papangkorn, 2015).…”
Section: Repetitionmentioning
confidence: 99%
“…Alzeebaree et al [37] conducted another research in an Iraqi environment to ascertain EFL teachers' beliefs about LA. He employed the questionnaire designed by Borg and Al-Busaidi [34] to obtain data from 116 EFL teachers (87 males and 29 females) with diverse academic and teaching backgrounds (diploma, bachelor's, master's, doctorate, as well as intermediate, secondary, and university levels).…”
Section: Teachers' Beliefs On Learner Autonomymentioning
confidence: 99%